Salvage surgery after definitive chemoradiotherapy through VATS for an initial unresectable locally advanced lung cancer: an alternative consolidative modality to radiotherapy? - Hsuan-Hsuan Yu; Yi-Wei Chen; Yi-Chen Yeh; Chien-Sheng Huang; Chao-Hua Chiu (Surgical Case Reports)
Abstract Background Definitive chemoradiotherapy (dCRT) is the first choice treatment for patients with locally advanced non-small cell lung cancer (NSCLC), but up to 35% of dCRT-treated tumors may have persistent or recurrent disease. Since the last decades, multimodality therapy showing potential for cure has become the mainstream for treatment of locally advanced NSCLCs, even some that were initially inoperable. Although salvage lung resection after dCRT has been reported with acceptable survivals, experiences in this respect are still limited. Other concerns remain debatable and inconclusive, such as dosage of radiation exposure, long interval between dCRT and surgery, and surgical comorbidity. Case presentation A 73-year-old male former smoker with diagnosis of right lower lobe of lung squamous cell carcinoma (SqCC) with multiple mediastinal lymphadenopathy, cT4N2M0, stage IIIB, received salvage right lower lobe + right middle lobe bilobectomy through video-assisted thoracoscopic surgery (VATS) after dCRT and adjuvant CRT to a total of 9000 cGy dosage of radiation. The interval from the 1st and 2nd ends of radiation to the salvage surgery was 980 and 164 days, respectively. The pre-operative forced expiratory volume in the first second was 2.33 L (101% predicted) and the diffusing capacity of the lungs for carbon monoxide was 56% predicted. The operating time was 6.5 h, and the total estimated blood loss was 50 ml. The patient was discharged on the 7th postoperative day without major complications or bronchopleural fistulas. The patient was still alive 42 months after the initial diagnosis of advanced N2 lung SqCC, and kept progression-free for 7 months after salvage lung resection. Conclusions Salvage lung resection performed long after high-dose radiation therapy of dCRT is technically feasible through VATS approach in a patient with initially inoperable cT4N2M0 stage IIIB NSCLC, and can be an alternative consolidative treatment for locally advanced NSCLC.